Quantum computation - Ekert, A (1996)
Quantum theory is vital for the next generation data processing devices. As computers become faster they must become smaller because of the finiteness of the speed of light. The history of computer technology has involved a sequence of changes from one type of physical realisation to another - from gears to relays to valves to transistors to integrated circuits and so on. The step to the molecular scale - The quantum level - will be next. Quantum theory is already important in the design of microelectronic components. Soon it will be necessary to harness quantum theory, rather than simply take it into account, to give data processing devices new functionality.